Strategies for the Fulfillment of Animal Nutritionist Competency Needs at Feedloters in Indonesia - Oktarina Nur Widyanti; Anggraini Sukmawati; Sukiswo Dirdjosuparto (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This study aimed to analyzing the Strategies for fulfillment animal nutritionist competency at feedloter in Indonesia. Methods in this study using Analytical Hierarchy Process (AHP). The data collection technique was conducted by judgement sampling to seven competent resource persons in the field of animal feed they are feed director in Ministry of Animal Health and Husbandry Republic of Indonesia, Chairman AINI and Director of the competency development and certification AINI period 2015-2019, Academics of lecturer in ransum formulation, operational manager and animal nutritionist in industry feedlot. The questions posed to the resource persons include factors, actors, goals and alternatives that most decisive in the fulfillment animal nutritionist competency at feedloter in Indonesia. The results of the AHP indicate that individual competence factors are critical in the strategy of the needs of livestock animal nutritionist. The Indonesian Association of Nutrition and Feed Technology (AINI) is actor the most influential in fulfilling the needs of animal nutritionist. AINI can conduct competency-based training, skills and knowledge development, latest technological innovations in ration making, and certification of competence of animal nutritionist to enhance individual competence. The alternative that a feedloter should do is to adapt the competency standards policy that exists in our country. It is concluded that the Strategies for fulfillment animal nutritionist competency at feedloter in Indonesiacan be fulfilled through the individuals as animal nutritionist, role of AINI increasing the competence of animal nutritionist, and the application of customized Indonesian welfare in Indonesia.